Hatchery culture of bivalves: a practical manual - Helm, M.M.; Bourne, N. (Rome (Italy), 2004)
Sumario (En)
Ilus.; 76 ref.
no. 471
Keywords: BIVALVIA; BIOLOGIA PESQUERA; TAXONOMIA; ANATOMIA ANIMAL; CULTIVO DE ALGAS; ALIMENTACION DE PECES; METAMORFOSIS; CRIA DE MOLUSCOS; ESTANQUES PISCICOLAS